Corporate Governance Country Assessment : Azerbaijan - World Bank (Washington, DC, 2014)
This report assesses Azerbaijan's corporate governance policy framework. It highlights recent improvements in corporate governance regulation, makes policy recommendations, and provides investors with a benchmark against which to measure corporate governance in Azerbaijan. It is an update of the 2005 Corporate Governance ROSC. In recent years, Azerbaijan's economy has experienced tremendous economic growth and the substantial institutional and legal change of earlier years has continued. New laws and regulations have improved legal protection for investors and the broader business environment. These include 2007 laws on insurance activity and internal audit, and 2008 amendments to the civil code and regulations that introduce board member duties and regulate related party transaction. Azerbaijan's Doing Business rankings have improved substantially since 2005. Enforcement and implementation of corporate governance has also begun to improve, especially in banks and companies with foreign investment. Foreign donors, including the International Finance Corporation (IFC) Azerbaijan Corporate Governance Project, have been helpful in this area.